International Purchasing in a Small Country: An Exploratory Study of Five Swedish Firms - Hallén, Lars (Journal of International Business Studies, 1982)
The extent of international purchasing in industrial firms is herein considered to be influenced by not only the market conditions but also the attitudes toward buying from abroad and the firm's competence for international transactions. To explore this possibility a subset of data from an international research project is used. Five cases encompassing relations to suppliers in 35 international supply markets are analyzed, and it is concluded that, in these cases, attitudes and competence requirements enable these firms to use foreign suppliers adequately with respect to the market conditions.